Accelerating Sustainable Proklim in The Food Resilience and Green Economy - Awatara, I Gusti Putu Diva; Setyono, Prabang; Widianto, Tri; Susanti, Nani Irma (Indonesian Journal of Geography, 2025)
This study aimed to develop a model for accelerating the transition to  green economy through the implementation of a climate village focused on food security. It introduced a children-friendly digital education program designed to enhance out-of-class learning on climate change mitigation and adaptation. This study also emphasized the integration of Proklim activities within designated areas to minimize the adverse effects of climate change. A survey method was conducted in Sukoharjo Regency with a sample of 160 respondents of Proklim activists. Primary data were collected using questionnaires, FGDs, and quantitative interviews, while secondary data were collected through documentation. The data were analyzed using geographic information systems, structural equation model PLS, vs code software, MySQL, construct, animate, and travel cost methods. The results showed that accelerating the transition to green economy through a food security-based climate village program involved a combination of adaptation, mitigation, and sustainability efforts. The adaptation measures focused on controlling drought, floods, and landslides, enhancing food security, and managing climate-related diseases. Meanwhile, mitigation efforts included effective waste management for both solid and liquid waste, adoption of renewable energy, conservation practices, energy efficiency, reduction of greenhouse gas emissions, agricultural innovation, and the preservation of vegetation cover. Sustainability was reinforced through the establishment of community groups, promotion of self-reliance, independent funding initiatives, gender-inclusive participation, capacity-building programs, external support, and the development of activities that generate social, economic, and environmental benefits. Digitalization in education is implemented through the Proklim digital platform, KampungIklim.com, which offers out-of-class learning resources on climate change mitigation and adaptation. Proklim activities serve as pilot sites for educational tourism, promoting sustainability by integrating economic value into existing initiatives, including the development of Proklim-based tourism villages.Received: 2024-08-15 Revised: 2024-11-15 Accepted: 2025-02-19 Published: 2025-04-29